Exploring the role of parents in supporting recreational book reading beyond primary school - Merga, Margaret (2014)
Levels of aliteracy have been found to rise in adolescence, and this article explores the potential influence of parents on this trend. The views of adolescent students who took part in semi-structured interviews for the West Australian Study in Adolescent Book Reading (WASABR) provide insight into how parental support may change in the adolescent years. Student perspectives support earlier findings that there is an expiration of parental encouragement in many cases, though this sometimes occurs as children are avid readers and thus the support is no longer deemed necessary. The experiences of students with parents who provided continued encouragement into adolescence are examined, with consistent characteristics emerging from the qualitative data. The article identifies optimal mechanisms through which parents can play an important role in supporting their children's recreational book reading into adolescence. © 2014 National Association for the Teaching of English.